2022
DOI: 10.3389/fpls.2022.877011
|View full text |Cite
|
Sign up to set email alerts
|

RING Zinc Finger Proteins in Plant Abiotic Stress Tolerance

Abstract: RING zinc finger proteins have a conserved RING domain, mainly function as E3 ubiquitin ligases, and play important roles in plant growth, development, and the responses to abiotic stresses such as drought, salt, temperature, reactive oxygen species, and harmful metals. RING zinc finger proteins act in abiotic stress responses mainly by modifying and degrading stress-related proteins. Here, we review the latest progress in research on RING zinc finger proteins, including their structural characteristics, class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 155 publications
(215 reference statements)
0
25
0
1
Order By: Relevance
“…Under abiotic stress, RING zinc finger proteins on the plasma membrane may function as sensors or ABA receptors in abiotic stress signaling. 40 In addition, C 2 H 2 zinc finger proteins function as key TFs in plant responses to a wide spectrum of stress conditions, including high temperature, salinity, light, and drought. WRKY TFs modulate seed germination and plant responses against abiotic and biotic stresses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under abiotic stress, RING zinc finger proteins on the plasma membrane may function as sensors or ABA receptors in abiotic stress signaling. 40 In addition, C 2 H 2 zinc finger proteins function as key TFs in plant responses to a wide spectrum of stress conditions, including high temperature, salinity, light, and drought. WRKY TFs modulate seed germination and plant responses against abiotic and biotic stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, RING zinc finger proteins play important roles in responses to abiotic stresses such as drought, salt, temperature, and ROS. Under abiotic stress, RING zinc finger proteins on the plasma membrane may function as sensors or ABA receptors in abiotic stress signaling . In addition, C 2 H 2 zinc finger proteins function as key TFs in plant responses to a wide spectrum of stress conditions, including high temperature, salinity, light, and drought.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc-finger proteins play a crucial role in responses to abiotic stimuli, such as drought, extreme temperatures, reactive oxygen species, salt, and toxic metals, in plants. They mostly operate as E3 ubiquitin ligases and contain a conserved RING domain ( Han et al., 2022 ); tify and GTP binding domain functions have also been identified in drought stress responses in cotton and Chinese cabbage ( Zhao et al., 2016 ; Chen et al., 2021 ) ( Supplementary Figure 1A and Supplementary Table 4 ). NCoEGs of GhHDT3D.2 contained a pentatricopeptide repeat, which plays an important role in drought, salt, and cold stress responses in Arabidopsis ( Jiang et al., 2015 ) ( Supplementary Figure 1B and Supplementary Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…ZFP transcription factors are widespread in the plant kingdom and play an instrumental role in plant growth, development, and response to environmental stress. ZFPs have been identified in many plant species [ 5 , 45 , 46 ]. However, no systematic studies have been reported on the four TaZFP subfamilies of T. aestivum .…”
Section: Discussionmentioning
confidence: 99%
“…However, plants have evolved multiple regulatory pathways involving many transcription factor families to receive and respond to different stress signals [ 2 , 3 ]. Various protein families are able to regulate plant physiological processes by modifying gene expression, altering signalling, and interfering with biosynthesis to improve their adaptability [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%